English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-05-08 08:08:14 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

It is (-1/3)e^(-3x) + C.

You can discover this using a u-substitution. Let u = -3x. Then du = -3 dx, or dx = du/-3. So we have

∫(e^(-3x)) dx = ∫e^u (du / -3) = (-1/3)∫(e^u) du.

Now, e^u is its own integral, so we get

(-1/3)∫(e^u) = (-1/3)e^u + C = (-1/3)e^(-3x) + C.

More generally, it is true that, for any nonzero real number k,

∫e^kx dx = (e^kx) / k + C.

2007-05-08 08:37:24 · answer #1 · answered by Anonymous · 0 0

The answer is:

(-1/3) (e^-3x) + C

You can check by taking the derivate of this, and you will get the original you started with.

2007-05-08 15:12:50 · answer #2 · answered by Anonymous · 0 0

Contant -3e^(-3x)

2007-05-08 15:12:14 · answer #3 · answered by gjmb1960 7 · 0 1

-1/3e^-3x

2007-05-08 15:11:12 · answer #4 · answered by Anonymous · 0 0

(e^(-3x+1)) / (-3x+1)

2007-05-08 15:12:05 · answer #5 · answered by Necrocell 1 · 0 1

fedest.com, questions and answers